1994
DOI: 10.1002/1097-0142(19940215)73:4<1251::aid-cncr2820730420>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Incremental angiogenesis assessed by color doppler ultrasound in the tumorigenesis of ovarian neoplasms

Abstract: Background. The crucial role of angiogenesis in tumor behavior has been studied extensively in vitro. The authors assessed the in vivo angiogenesis in ovarian neoplasms by color Doppler ultrasound and waveform analysis. Methods. The intratumor artery resistance index (RI) of 222 ovarian neoplasms referred for color Doppler ultrasound evaluation was measured, and the corresponding histopathologic diagnosis was recorded. Results. Satisfactory intratumor artery waveforms were obtained at an average of 1.12 sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…In addition, up to 17% of BOTs appear as unilocular smooth anechoic cysts without endophytic papillary growth [17,[35][36][37]39] resulting in low sensitivity of ultrasonography in the diagnosis of BOT. Some authors observed a gradual decrease in the mean value of resistance index (RI) and pulsatility index (PI) from benign tumors, via BOT, to invasive ovarian malignancies [40][41][42]. Other authors reported significant differences in PI and RI values between BOT and benign tumors, while no difference was observed between BOT and malignant tumors [13,26,34,35,39].…”
Section: Ultrasonographymentioning
confidence: 99%
“…In addition, up to 17% of BOTs appear as unilocular smooth anechoic cysts without endophytic papillary growth [17,[35][36][37]39] resulting in low sensitivity of ultrasonography in the diagnosis of BOT. Some authors observed a gradual decrease in the mean value of resistance index (RI) and pulsatility index (PI) from benign tumors, via BOT, to invasive ovarian malignancies [40][41][42]. Other authors reported significant differences in PI and RI values between BOT and benign tumors, while no difference was observed between BOT and malignant tumors [13,26,34,35,39].…”
Section: Ultrasonographymentioning
confidence: 99%
“…21,23,26,28Y30 Six studies were nonblinded and prospective with a small population, but included sufficient experimental details, proper diagnostic tests and diagnostic reference standards. 20,21,23,26,28,30 Of the 12 included studies, 6 had high 20,21,23,26,28,30 methodological quality, satisfying 55% or higher of the criteria for study quality and with an Oxford Evidence level of 2B. 11 However, 6 studies 19,22,24,25,27,29 were classified as level 3B because details of the patients, including age, were not reported and because they met lower than 50% of the quality criteria.…”
Section: Studies Descriptionmentioning
confidence: 99%
“…4 The intensity of neovascularization may depend on individual tumor characteristics. Wu et al 25 documented an incremental decrease of the RI in ovarian neoplasms, which might reflect the increase in angiogenesis intensity as an indication of malignant potential. Because of deficient smooth muscle layer in the media of tumor vessels and presence of arteriovenous shunting, the vessels in malignant tumors have low impedance that leads to high diastolic flow and low systolic-diastolic difference (lower RI).…”
Section: Discussionmentioning
confidence: 98%